Estudo de método alternativo para determinação da demanda química de oxigênio (DQO) por meio de eletrodo Cu/CuO - Valerio, Daniele Cerri (2018)
In function of the growing demand for activities that minimize the impacts environmental created by waste, the effluent analysis are extremely important to determine the intensity of contamination in water bodies. Due to the large part these effluents have materials rich in nutrients, with C, N e P and others organics and inorganics components, it is used to determination the chemical oxygen demand (COD), methodology used to measure the amount of oxygen consumed by certain substances. In this context, the objective of this study was to develop electrochemical method to determination the Chemical Oxygen Demand using copper electrode. The electrode was prepared using accessible chemical reagents and in small quantities. By means of measures electrochemical the performance test was performed using glucose. The obtained results demonstrated the formation of a cooper oxide layer that allows the electrode application, whereas, the copper oxidizes organic compounds in alkaline medium, such as carbohydrates. Performing the repeatability test using standard glucose solution, the method accuracy was 2.13% and a detection limit of 146 mg L-1. It was possible to compare the fructose, sucrose and sorbitol compounds in order to evaluate the copper electrode answer by the cyclic voltammetry in the same experimental conditions for glucose. The Cu / CuO electrode presents satisfactory analytical response that was used to study chemical oxygen demand by addition of standard, comparing with the official method. However, because the values found in the samples by the official method were below the value of the recommended range for the analytical range, the results dispersion (RSD) among others, it was not possible to correlate the methods.